ACE - The Tie That Binds - Robert A. Jarnagin (Journal of Applied Communications, 1978)
AAACE Origin and Development - 1913-1967, by Robert A. Jarnagin, commemorated the 50th annual conference of the American Association of Agricultural College Editors, July 12-15, 1966, at the University of Georgia.